Efficacy of docetaxel plus ramucirumab as palliative third-line therapy following second-line immune-checkpoint-inhibitor treatment in patients with non-small-cell lung cancer stage IV: $hWolfgang M. Brueckl, Martin Reck, Achim Rittmeyer, Jens Kollmeier, Claas Wesseler, Gunther H. Wiest, Petros Christopoulos, Amanda Tufman, Petra Hoffknecht, Bernhard Ulm, Fabian Reich, Joachim H. Ficker and Eckart Laack - Brückl, Wolfgang M.; Reck, Martin; Rittmeyer, Achim; Kollmeier, Jens; Wesseler, Claas; Wiest, Gunther H.; Christopoulos, Petros; Tufman, Amanda; Hoffknecht, Petra; Ulm, Bernhard; Reich, Fabian; Ficker, Joachim H.; et al. (Clinical medicine insights. Oncology, 2020)
Background: Antiangiogenic agents have been shown to stimulate the immune system and cause synergistic effects with chemotherapy. Effects might be even stronger after immune-checkpoint-inhibitor (ICI) therapy. The purpose of this analysis was to evaluate the efficacy of ramucirumab plus docetaxel (R + D) as third-line treatment after failure of a first-line platinum-based chemotherapy and a second-line ICI treatment in patients with non-small-cell lung cancer (NSCLC) stage IV. Methods: Retrospective data were collected from 9 German thoracic oncology centers. Only patients who had received at least 1 cycle of third-line R + D were included. The numbers of cycles, objective response rate (ORR), progression-free survival (PFS), and overall survival (OS) were investigated. Results: Sixty-seven patients met the criteria for inclusion. Third-line treatment with R + D achieved an ORR of 36% and a disease control rate (DCR) of 69%. Median PFS for third-line therapy was 6.8 months with a duration of response (DOR) of 10.2 months. A median OS of 29 months was observed from the start of first-line therapy with a median OS of 11.0 months from the start of third-line treatment. No unexpected toxicities occurred. Conclusion: R + D is a highly effective and safe third-line treatment after failure of second-line programmed cell death protein 1/programmed cell death-ligand 1 (PD1/PD-L1)-derived ICI therapy irrespective of NSCLC histology. As there may be synergistic effects of second- and third-line treatments, this sequence is a very suitable option for patients not treated with first-line ICI. In addition, R + D should continue to be investigated as a second-line treatment option after failure of chemotherapy plus ICI in the palliative first–line treatment.
Gesehen am 26.10.2020